Lipid‐coated bismuth nanoflower as the thermos‐radio sensiti for therapy of lung metastatic breast cancer: Preparation, optimisation, and characterisation - Shushu Xue; Junrong Jiao; Si Miao; Lijun Wang; Yang Liu; Qingjie Zhang; Qiyue Wang; Yu Xi; Yuanyuan Zhang (IET Nanobiotechnology)
Abstract Lung metastatic breast cancer (LMBC) leads to a large number of deaths in women with breast cancer, and radiotherapy has been considered the common assay for tumour therapy except for surgery. However, radiotherapy still faces problems of low efficiency due to resistance and easily induced side effects. Here, the authors designed lipid‐decorated bismuth‐based nanoflowers (DP‐BNFs) as both a radiosensitiser and a photothermal therapy agent for LMBC treatment. The BNFs were prepared by oxidation of bismuth nitrate and subsequent reduction using sodium borohydride. The preparation parameters and formulation of DP‐BNFs were optimised via a single‐factor experiment, with the factors including reaction temperature, a molar ratio of reducing agents, and the types and amount of decorated lipid materials. The result indicated that the BNFs prepared at 170°C with the Bi/NaBH4 ratio of 1:0.7 exhibited the best yield and particle size around 160 nm. After being spray dried with lactose to prepare dry powder inhalation (DP‐BNF@Lat‐MPs), their effects on improving therapeutic efficiency of the radiotherapy and photothermal therapy combination were measured using the western blot assay to determine the tumour apoptosis. In a word, DP‐BNF@Lat‐MPs could be a novel inhalable integrated microsphere that provides a new possibility for thermoradiotherapy of LMBC.